The outcomes of Ilizarov treatment in aseptic nonunions of the tibia stratified by treatment strategies and surgical techniques - Szelerski, Łukasz (Sci Rep, 2020)
Nonunions of the tibia, particularly those located in the distal third of the bone, are relatively common in clinical practice. There is no gold standard for the treatment of nonunions of the tibia. The purpose of our study was to assess the results of treatment with the Ilizarov method in patients with aseptic nonunions of the tibia, depending on the employed treatment strategies and surgical techniques. A total of 75 patients with Ilizarov treatment of aseptic nonunions of the tibia were evaluated in the study. The patients’s mean age at the beginning of treatment was 46 years. The mean follow-up period was 10 years and 11 months. The evaluated patients underwent either closed technique or open technique. The operators used one of two treatment strategies: neutral fixation without compression or continued compression. The following were assessed: rates of union, ASAMI bone scores, ASAMI functional scores, treatment time, complications, duration of hospital stay. Bone union was achieved in all of the 75 evaluated patients. The results of most analyses showed no significant differences in the assessed variables, except for the ASAMI functional scores, which were higher in the group of patients who underwent closed surgery (Me = 6.00 vs. Me = 4.00). We observed better ASAMI functional score outcomes in the patients who underwent closed fixation than in the open fixation group. The different surgical techniques and treatment strategies had no effect on the number of complications, rates of bone union, length of hospital stay, duration of Ilizarov treatment, or ASAMI bone scores. For managing nonunions of the tibia we recommend the technique of closed fixation without continued compression. The Ilizarov method in the treatment of nonunions of the tibia gives good outcomes.